Establishment of a lectotype for the species Plesiochelys langii Rütimeyer, 1873 - Anquetin, Jérémy (PeerJ, 2015)
Background. In a recent paper, we proposed a lectotype for the species Plesiochelys langii Rütimeyer, 1873. However, we failed to register this publication in ZooBank as required by the International Commission on Zoological Nomenclature (ICZN) for electronic publication. Although our conclusions remain unchanged, this particular nomenclatural act cannot be considered as published under ICZN regulations. Results. The present work fulfills the requirements of the ICZN for a lectotype designation and has been registered in ZooBank.
Keywords: Plesiochelys langii; Plesiochelys etalloni; Plesiochelyidae; Lectotype; Nomenclature